Formation processes and quality evaluation of natural zeolite deposits in dynamic diagenetic systems of the Janggi Basin, southeastern Korea: implications for zeolite ore exploration - Changyun Park; Hae-in Lee; Jae-Hwan Kim; Donghoon Chung; Yongmoon Lee; Soojin Lee; Tae-Hee Koo; Insung Kang; Ho Sim; Woohyun Choi; Sung Man Seo (Mineralium Deposita, 2026)

Psychrotrophic lactic acid bacteria enhance microbial safety in kimchi: Evidence from untargeted metabolomics - Daun Kim; In Min Hwang; Ho Myeong Kim; Seul-Gi Jeong; Hae Woong Park (International Journal of Food Microbiology, 2026)

Anti-inflammatory effect of a Capsosiphon fulvescens (Chlorophyta) extract obtained by subcritical water extraction on lipopolysaccharide-induced RAW 264.7 cells - Ju-Hye Im; Su-mi Park; Yu-Jin Heo; Mi-Kyung Lee; Hae-In Lee (Journal of Applied Phycology, 2026)

Biocontrol potential of beauvericin produced in a submerged culture of Beauveria bassiana 331R against cotton aphid Aphis gossypii - Jong-Cheol Kim; In Min Hwang; Ho Myeong Kim; Seulbi Kim; Hyunbok Song; Seulki Kim; Tae Young Shin; Taek Su Shin; Soo‑Dong Woo; Hae Woong Park (BioControl, 2026)

Precursor feeding strategy of oxydifficidin production in submerged culture of Bacillus velezensis 8–2 and its biological control potential against soft rot disease - Seulbi Kim; Ho Myeong Kim; In Min Hwang; Seul-Gi Jeong; Chang Hee Jeong; Jin-Cheol Kim; Hae Woong Park (Pesticide Biochemistry and Physiology, 2026)

Editor's note to “Stand age-driven tree size variation and stand type regulate aboveground biomass in alpine-subalpine forests, South Korea” [Sci. Total Environ. 915 (2024), 170063] - Yong-Ju Lee; Go-Eun Park; Hae-In Lee; Chang-Bae Lee (Science of The Total Environment, 2025)

Evaluation of polystyrene nanoplastic removal from aquatic environments and antibacterial activity against various harmful bacteria using jellyfish extract - Joo Eun Shim; Hyesoo Lee; In Hae Park; Min-Kyeong Yeo (Molecular & Cellular Toxicology, 2025)

Baricitinib-loaded separable microneedle array patch (S-MAP) based on hyaluronic acid for alopecia areata therapy - Da In Jeong; Song Yi Lee; Sungyun Kim; Su-Min Jo; HeeSeon Yang; Jieun You; ChaeRim Hwang; Ji Won Huh; Yeoung Eun Choi; Wonjun Jo; In-Jeong Choi; Hae-Jin Hu; et al. (Carbohydrate Polymers, 2025)

Nano-TiO2 removal using jellyfish extracts and an assessment of aquatic toxicity - In Hae Park; Joo Eun Shim; Hyesoo Lee; Ki Heon Jeong; Min-Kyeong Yeo (Molecular & Cellular Toxicology, 2025)

Development of high-resolution melting markers for assessment of the hybridization between Mauremys sinensis and Mauremys reevesii - Hae-jun Baek; Soo-In Lee; Chang-Deuk Park; Ju-Duk Yoon (Conservation Genetics Resources, 2025)

Tribuli Fructus alleviates 1-methyl-4-phenyl 1,2,3,6-tetrahydropyridine (MPTP)-induced Parkinson’s disease by suppressing neuroinflammation via JNK signaling - Jin Hee Kim; Eugene Huh; Hyeyoon Eo; Jin Se Kim; Youngji Kwon; In Gyoung Ju; Yujin Choi; Hae-Jee Yoon; So-Ri Son; Dae Sik Jang; Seon-Pyo Hong; Hi-Joon Park; et al. (Metabolic Brain Disease, 2024)

Olaparib synergically exacerbates the radiation-induced intestinal apoptosis in mice - Sohee Jeong; Jeongmin Lee; Jun Hong Park; Yeonghoon Son; Hae-June Lee; Changjong Moon; In Sik Shin; Joong Sun Kim; Sohi Kang (Molecular & Cellular Toxicology, 2024)

Natural peloids originating from subsea depths of 200 m in the hupo basin, South Korea: physicochemical properties for potential pelotherapy applications - Changyun Park; Jae-Hwan Kim; Woohyun Choi; Daeyoung Kim; Sang-Gun No; Donghoon Chung; Hae-in Lee; Seungbin Seo; Sung Man Seo (Environmental Geochemistry and Health, 2024)
The present study firstly reports surface sediment from the subsea depth of 200 m as a potential natural peloid. The fine-silt sediment exhibited a consistent clay mineral composition dominated by illite, chlorite, kaolinite, and diatomite. The most abundant clay mineral was illite/mica, with other minerals loosely packed in a face-to-face orientation. The thermal conductivity, specific heat capacity, and cation-exchange capacity of the sediment were in the range 0.855–0.885 W/m K, 2.718–2.821 J/g °C, and 23.06–32.96 cmol/kg, respectively. The concentrations of most toxic elements in the sediment were considerably lower than the limits set by domestic cosmetic regulations and other international standards. The analyzed samples exhibited similar properties to those of previously reported peloids, thus making them suitable for use in the field of pelotherapy; furthermore, the consistency in data across a wide peloid-distribution area is expected to enable economically viable mining. Future investigations should aim to to evaluate the long-term effects on the skin, the bioavailability of potentially hazardous substances, and the therapeutic efficacy for various skin conditions.

Low-dose-rate gamma radiation aggravates titanium dioxide nanoparticle-induced lung injury in mice - Sohi Kang; Hae-June Lee; Yeonghoon Son; Min Ji Bae; Wol Soon Jo; Jun Hong Park; Sohee Jeong; Changjong Moon; In-Sik Shin; Chang Geun Lee; Joong Sun Kim (Molecular & Cellular Toxicology, 2024)

Stand age-driven tree size variation and stand type regulate aboveground biomass in alpine-subalpine forests, South Korea - Yong-Ju Lee; Go-Eun Park; Hae-In Lee; Chang-Bae Lee (Science of The Total Environment, 2024)

Utilization of coffee waste as a sustainable feedstock for high-yield lactic acid production through microbial fermentation - Seulbi Kim; Jong-Cheol Kim; Yeong Yeol Kim; Jung Eun Yang; Hee Min Lee; In Min Hwang; Hae Woong Park; Ho Myeong Kim (Science of The Total Environment, 2024)

Correction to: Rapid analysis of insecticidal metabolites from the entomopathogenic fungus Beauveria bassiana 331R using UPLC-Q-Orbitrap MS - Jong-Cheol Kim; In Min Hwang; Ho Myeong Kim; Seulbi Kim; Teak Su Shin; Soo-Dong Woo; Hae Woong Park (Mycotoxin Research, 2024)

Rapid analysis of insecticidal metabolites from the entomopathogenic fungus Beauveria bassiana 331R using UPLC-Q-Orbitrap MS - Jong-Cheol Kim; In Min Hwang; Ho Myeong Kim; Seulbi Kim; Teak Su Shin; Soo-Dong Woo; Hae Woong Park (Mycotoxin Research, 2024)

Facile and rapid fabrication of wearable biosensors via femtosecond laser-directed micro-patterning with large-sized reduced graphene oxide for physiological monitoring - Hae-In Moon; Sungil Kim; Jeong Eun Byun; Young Won Kim; Yeon Wook Jung; Seung Geun Jo; Yujin Shin; Yeoul Kang; Sang Jun Kim; Eun-Su Lee; Hyung-Jong Lee; Min-Cheol Oh; et al. (Chemical Engineering Journal, 2024)

Reduced cellular process and developmental process genotoxicity of polystyrene nanoplastics in zebrafish embryogenesis using Aurelia aurita proteins - In Hae Park; Sun Woo Geum; Min-Kyeong Yeo (Molecular & Cellular Toxicology, 2023)

Physical and biomimetic treatment methods to reduce microplastic waste accumulation - Hyesoo Lee; Joo Eun Shim; In Hae Park; Kyung Sil Choo; Min-Kyeong Yeo (Molecular & Cellular Toxicology, 2023)

Metacognitive beliefs predict early response to pharmacological treatment in patients with obsessive–compulsive disorder - Chun Il Park; Hae Won Kim; Sumoa Jeon; Eun Hee Hwang; Jee In Kang; Se Joo Kim (Psychopharmacology, 2020)

Improvement of blood culture contamination rate, blood volume, and true positive rate after introducing a dedicated phlebotomy team - Moonsuk Bae; Hae In Kim; Joung Ha Park; Byung-Han Ryu; Jeonghyun Chang; Heungsup Sung; Jiwon Jung; Min Jae Kim; Sung-Han Kim; Sang-Oh Lee; Sang-Ho Choi; Yang Soo Kim; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Lysine deacetylase inhibition attenuates hypertension and is accompanied by acetylation of mineralocorticoid receptor instead of histone acetylation in spontaneously hypertensive rats - Young Mi Seok; Hae Ahm Lee; Kwon Moo Park; Mi-Hyang Hwangbo; In Kyeom Kim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Erratum to: Nitrospirillum irinus sp. nov., a diazotrophic bacterium isolated from the rhizosphere soil of Iris and emended description of the genus Nitrospirillum - Eu Jin Chung; Tae Soon Park; Kyung Hyun Kim; Che Ok Jeon; Hae-In Lee; Woo-Suk Chang; Zubair Aslam; Young Ryun Chung (Antonie van Leeuwenhoek, 2015)

Nitrospirillum irinus sp. nov., a diazotrophic bacterium isolated from the rhizosphere soil of Iris and emended description of the genus Nitrospirillum - Eu Jin Chung; Tae Soon Park; Kyung Hyun Kim; Che Ok Jeon; Hae-In Lee; Woo-Suk Chang; Zubair Aslam; Young Ryun Chung (Antonie van Leeuwenhoek, 2015)

Erratum to: Boron availability alters its distribution in plant parts of tomato - Eun-Young Choi; Hae-In Park; Jin-Hee Ju; Yong-Han Yoon (Horticulture, Environment, and Biotechnology, 2015)

Age-related change in γH2AX of Drosophila muscle: its significance as a marker for muscle damage and longevity - Ho-Jun Jeon; Young-Shin Kim; Joung-Sun Park; Jung-Hoon Pyo; Hyun-Jin Na; In-Joo Kim; Cheol-Min Kim; Hae Young Chung; Nam Deuk Kim; Robert Arking; Mi-Ae Yoo (Biogerontology, 2015)

Boron availability alters its distribution in plant parts of tomato - Eun-Young Choi; Hae-In Park; Jin-Hee Ju; Yong-Han Yoon (Horticulture, Environment, and Biotechnology, 2015)

A new flavonoid glycoside from the root bark of Morus alba L. - Ji-Hae Park; Ye-Jin Jung; Jae-Woo Jung; Sabina Shrestha; Dong Wook Lim; Daeseok Han; Nam-In Baek (Natural Product Research, 2014)

Flavonoids from Lindera glauca Blume as low-density lipoprotein oxidation inhibitors - Gyu-Won Huh; Ji-Hae Park; Ji-Hyun Kang; Tae-Sook Jeong; Hee Cheol Kang; Nam-In Baek (Natural Product Research, 2014)

Phenolic components from Rhus parviflora fruits and their inhibitory effects on lipopolysaccharide-induced nitric oxide production in RAW 264.7 macrophages - Sabina Shrestha; Dae-Young Lee; Ji-Hae Park; Jin-Gyeong Cho; Dong-Sung Lee; Bin Li; Youn-Chul Kim; Geum-Soog Kim; Myun-Ho Bang; Nam-In Baek (Natural Product Research, 2013)

Immune responses in mice vaccinated with virus-like particles composed of the GP5 and M proteins of porcine reproductive and respiratory syndrome virus - Hae-Mi Nam; Kyung-Sil Chae; Young-Jo Song; Nak-Hyung Lee; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Kun-Ho Seo; Sang-Moo Kang; Min-Chul Kim; In-Soo Choi (Archives of Virology, 2013)

Identification of genetic diversity of porcine Norovirus and Sapovirus in Korea - Young-Jo Song; Je-Nam Yu; Hae-Mi Nam; Hyoung-Rok Bak; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Kun-Ho Seo; In-Soo Choi (Virus Genes, 2011)

Expression of Interferon Inducible Genes Following Hantaan Virus Infection as a Mechanism of Resistance in A549 Cells - Jae-Hwan Nam; Kyung-A Hwang; Cheong-Hee Yu; Tae-Hoon Kang; Jae-Young Shin; Woo-Young Choi; In-Beom Kim; Young-Ran Joo; Hae-Wol Cho; Keun-Yong Park (Virus Genes, 2003)